Hiding Secret image and text in image based (DWT) and Chaos Theory - Doaa mahmood abass , Assist. Prof. Dr. Ali Hussien Mary, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Steganography is a hiding information which is the science and art of secret communication. It allows the transmission of confidential information and the concealment of the presence of the message itself in content such as video, audio or image to protect the information sent from intruders and unwanted recipients. In the past decade, a variety of researches have been conducted on schematics of steganography in both the spatial and transformation domain. In this research, an image of steganography system that hides medical image and secret key inside another color cover image was proposed using a combination of Discrete Wavelet Transform Technique (DWT) , Particle Swarm optimization , and chaotic theory. Matlab 2018 has been used to implement the proposed algorithm. Based on the performance indexes that are calculated for each method, all the proposed methods achieve a good performance. Thus, the proposed algorithms achieved the steganographic goals that are designed for this purpose